AN IN-DEPTH EXPLORATION OF LEFT EYE BLURRED VISION: CAUSES, MECHANISMS, AND CLINICAL INSIGHTS - Hafsah US; Fajar Rahmat Aziz; Andro Ruben Runtu; Syafaat Rudin; Muslahuddin As'ad (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study comprehensively explores blurred vision in the left eye, unraveling its intricate web of anatomy, physiology, and contributing factors. The left eye's complex structure, involving the cornea, iris, lens, retina, and optic nerve, is meticulously dissected to discern their roles in visual perception. Blurred vision transcends optical distortion, presenting a dynamic spectrum of symptoms and characteristics. From difficulties in focusing to haziness and distorted shapes, this visual impairment poses challenges that extend beyond the physical realm, influencing daily activities and psychological well-being. The multifactorial etiology of blurred vision is elucidated, encompassing refractive errors, corneal disorders, lens anomalies, retinal and optic nerve pathologies, and psychological influences. Diagnostic methods, ranging from traditional eye examinations to psychological assessments, are discussed, providing a comprehensive toolkit for accurate assessments. Real-world implications underscore the psychosocial impact, emphasizing the need for holistic patient care. This study's significance lies in its consolidated synthesis of existing knowledge, offering a valuable resource for clinicians, researchers, and educators in the field of ophthalmology. Including case studies enriches practical insights, bridging the gap between theory and clinical application. Visual aids, such as tables, enhance accessibility, ensuring broad dissemination of this complex information. In conclusion, this study advances our understanding of blurred vision in the left eye and sets the stage for future research endeavors, fostering continuous improvements in diagnosis and tailored interventions.